How does vessel curvature influence drug release from DES and drug transport in arterial tissue? - Escuer Gracia, Javier; Peña, Estefanía; Aznar, Irene; Martínez, Miguel Ángel (Jornada de Jóvenes Investigadores del I3A, 2019)
Several computational models of transport of drugs eluted from drug-eluting stents (DES) in curved arteries were developed in order to investigate the influence of the arterial curvature and complex geometries on drug transport in the blood flow and in the arterial wall.